Chronic Hypertension in Women after Perinatal Exposure to Preeclampsia, Being Born Small for Gestational Age or Preterm. Issue 2 (20th February 2017) - Lindström, Linda; Skjærven, Rolv; Bergman, Eva; Lundgren, Maria; Klungsøyr, Kari; Cnattingius, Sven; Wikström, Anna‐Karin
Abstract: Background: There is an established association between adverse events during perinatal life and chronic hypertension in adult life. However, disadvantageous conditions often co‐exist in the same pregnancy. We investigated single and joint perinatal exposure to preeclampsia, being born small for gestational age (SGA) or preterm and subsequent risk of chronic hypertension. Methods: The study population consisted of 731 008 primiparous women from Norway and Sweden registered in the Medical Birth Registers, both as infants and as first time mothers between 1967–2009 (Norway) and 1973–2010 (Sweden). Risk of chronic hypertension in early pregnancy was calculated in women with perinatal exposures to preeclampsia, born SGA or preterm by log‐binominal regression analysis, and adjusted for maternal age and level of education in the first generation. Results: The rate of chronic hypertension was 0.4%. Risk of chronic hypertension was associated with single perinatal exposure to preeclampsia, being born SGA or preterm with adjusted relative risk (95% confidence interval, CI) of 2.2 (95% CI 1.8, 2.7), 1.1 (95% CI 1.0, 1.3), and 1.3 (95% CI 1.0, 1.5) respectively. The risks increased after joint exposures, with an almost fourfold risk increase after perinatal exposure to preeclampsia and preterm birth. Additional adjustment for BMI and smoking in the second generation in a subset of the cohort only had a minor impact on the results. Conclusions: Perinatal exposure to preeclampsia, being born SGA or preterm is independently associated with increased risk of chronic hypertension. The highest risk was seen after exposure to preeclampsia, especially if combined with SGA or preterm birth.